Health and safety practices and policies concerning human exposure to RF/microwave radiation - Lin, James C. (Frontiers in Public Health, 2025)
Concerns about the impacts on the public health and safety of radiofrequency (RF) exposure are increasing with the rapid proliferation of cellular mobile telecommunication systems and devices. There is also lack of confidence surrounding the applicability of stated health safety rules, limits and guidelines for RF exposure including their use for 5G and the expected 6G. This paper: (1) considers the currently promulgated standards for safe human exposure to RF radiation, (2) examines assumptions underlying the standards, (3) describes the roles of the military industrial complex in influencing research on the health effects and standards setting for safety levels, (4) discusses the engagement of an industry-regulatory complex, (5) explains the interaction between ICNIRP and the WHO-EMF, (6) scrutinizes recent publications of WHO-EMF commissioned systematic reviews, and (7) concludes with some observations on an apparent paradigm shift.